AN "IN VITRO" STUDY ON THE CANAL SHAPING CAPACITY OF PRO TAPER FILES - Ionela Elisabeta Ciobanu; Andreea Cristiana Didilescu; Alexandru Andrei Iliescu; George Adrian Ciobanu; Andrei Iliescu (Romanian Society of Oral Rehabilitation, 2013)
The aim of this study was to examine the risk of stripping perforation of the root canal while shaping with Pro Taper manual system. Resin blocks were instrumented with manual Pro Taper files then photographed. The pictures were entered into a computer program to perform measurements. At 8 mm from the apex, all ProTaper files led to a significant transportation of the inner wall of the curvature compared to the control (p < 0.05). At 5 mm, ProTaper files ranging from S2 to F3 presented important statistical differences compared to the control. Also, file F3 achieved a transportation of 1.89 of the inner wall compared to file S1. At 2mm, the finishing files F2, F3 incurred significant increases of the total diameter (p<0.05) in contrast with both the control and files S1 and S2. ProTaper system removes a large amount of root dentin increasing the risk of stripping perforation.